2005
DOI: 10.1177/095632020501600503
|View full text |Cite
|
Sign up to set email alerts
|

Novel Phorbol Esters Exert Dichotomous Effects on Inhibition of HIV-1 Infection and Activation of Latent HIV-1 Expression

Abstract: Two new phorbol esters, NPB-11 (12-O-methoxymethylphorbol-13-decanoate) and NPB-15 (12-O-benzyloxymethylphorbol-13-decanoate) were synthesized. The compounds exhibited potent anti-HIV-1 activity and low cytotoxicity in MT-4 cells by MTT assay even at a high concentration [50% cytotoxic concentrations (CC50) were 8.32 and 4.39 microg/ml, respectively]. Two inhibitors strongly suppressed HIV-1 (IIIB strain) replication in MT-4 cells with a 50% effective concentration (EC50) of 1.3 and 0.27 ng/ml, respectively. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A subsequent study on the modes of action of 19 and 21 indicated that their anti-HIV activities are partially explained by downregulation of the CD4 receptor and the expression of HIV-1 co-receptors CXCR4 and CCR5 in the host cells. 47) In addition, 19 and 21 were found to upregulate HIV-1 expression in latently infected cell lines and to induce cell death in HIV-1 infected cells. Although their potential as tumor promoters still raises concerns about their therapeutic use, 19 and 21 are promising as adjuvants in combination with HAART.…”
Section: Analogs With Therapeutic Potential In Aidsmentioning
confidence: 99%
“…A subsequent study on the modes of action of 19 and 21 indicated that their anti-HIV activities are partially explained by downregulation of the CD4 receptor and the expression of HIV-1 co-receptors CXCR4 and CCR5 in the host cells. 47) In addition, 19 and 21 were found to upregulate HIV-1 expression in latently infected cell lines and to induce cell death in HIV-1 infected cells. Although their potential as tumor promoters still raises concerns about their therapeutic use, 19 and 21 are promising as adjuvants in combination with HAART.…”
Section: Analogs With Therapeutic Potential In Aidsmentioning
confidence: 99%